Employment effects of R&D and innovation: Evidence from small and medium-sized firms in emerging markets - Rajeev K. Goel; Michael A. Nelson (Kiel Institute for the World Economy (IfW), 2021)
This paper studies the impact of research and development (R&D) and innovation on employment growth, focusing on small and medium-sized firms. Employment effects of R&D and innovation are unclear a priori as process innovation may be labor-saving or labor might have complementarities with other inputs. Employing firm-level data from 125 nations, results show that both R&D and innovation increased employment growth, suggesting that innovation was either capital-saving or labor had strong complementarities with other inputs. Upon splitting the sample into growing and contracting firms showed that contracting firms benefit from innovation but not from R&D. In other findings, sole proprietorships, larger firms, firms with relatively more experienced managers, firms with females as top managers, and firms facing the threat of informal competition had lower employment growth, while foreign-owned and government-owned enterprises have positive influences on employment growth. Finally, employment growth in shrinking firms was boosted in nations with greater economic freedom, but this growth is undermined by informal sector competition.
Keywords: L2; O3; O5; 330; R&D; innovation; employment growth; managerial experience; foreign ownership; government ownership; economic freedom; emerging markets